The Role of the Braille Corner Service in Creating Social Inclusion Services in the Malang City Public Library - Inawati; Rista Tanaya Pawestri (Literatify: Trends in Library Developments, 2023)
This research aims to determine the role of the Braille Corner service in creating social inclusion services in the Malang City Public Library. Social inclusion services in this research were measured using three aspects, namely connectivity, content, and community. According to Miles and Huberman, this type of descriptive research uses a qualitative approach, and data analysis techniques go through three stages: data reduction, data presentation, and drawing conclusions. The research results based on three aspects are (1) the Braille Corner service has adequate facilities and infrastructure to create inclusive services, apart from that the connectivity indicators also have various efforts to reach blind users such as by collaborating with various disability social communities, (2) aspects content by providing and developing library collections, extraordinary collections for the blind such as audiobooks, braille books, guiding blocks and so on. and (3) the human aspect, namely that librarians are equipped with special competencies that will help blind users in utilizing braille reading corner services in Malang city public libraries. From these three aspects, the Braille Corner service creates social inclusion services for the community, especially for blind users at the Malang City Public Library.